Moving images on the margins : experimental film in late socialist East Germany - Howes, Seth (Screen cultures., 2019)
In the German Democratic Republic during the 1970s and 1980s, more than two hundred films and videos, many of them experimental, were made outside government-run institutions despite legal restrictions on independent filmmaking, and despite the state-owned DEFA studio system's resistance to experimental film. Many were by professional artists who incorporated their painted, sculpted, and performed works in their films and then re-integrated their films into their other artistic endeavors. In addition to showing and debating their films informally in private, these artists worked within existing institutions, establishing annual meetings at Dresden's Academy of Fine Arts, publishing on experimental film in official journals, and even exhibiting films at the Academy of Arts in Berlin. Though pursued as political subversives by the Stasi and dismissed as dilettantes by older critics, these artists frequently engaged their detractors in open debate, advancing their creative itineraries by exposing conceptual problems lurking in the histories of art and cinema. Through extensive archival research, formal analyses of over a dozen films, and interpretation of their relation to their creators' work in other media, Seth Howes documents the rich allusiveness and intellectual probity of experimental filmmaking in East German socialism's final years. Individual chapters examine Lutz Dammbeck's incorporation of painting, dance, literature, and experimental film into a critique of the (mass- )mediation of experience; the Autoperforationsartisten's use of film to problematize the notion of the "performance document"; Greifswald-based artists' integration of film into mail-art projects that crossed political borders and boundaries between media; and Yana Milev's blending of film and installation art to theorize the organization and segmentation of urban spaces. Seth Howes is Assistant Professor of German and Director of Graduate Studies in the Department of German and Russian Studies at the University of Missouri